New teaching strategies using ict tools in higher education - Huarcaya Aliaga, Ruth (2017)
This article aims to contribute to the teaching practice, significant learning using mobile resources in the development of new teachinglearning strategies, ICT tools, in order to innovate in the different communication codes.